2008
DOI: 10.1007/s00411-008-0200-1
|View full text |Cite
|
Sign up to set email alerts
|

Irradiation leads to sensitization of hepatocytes to TNF-α-mediated apoptosis by upregulation of IκB expression

Abstract: This study aimed to reveal the pathophysiological signalling responsible for radiation-induced sensitization of hepatocytes to TNF--mediated apoptosis. I B was upregulated in irradiated hepatocytes. Administration of I B antisense oligonucleotides prior to irradiation inhibited occurrence of apoptosis after TNF-administration. Caspases-8, -9 and -3 activities were increased in irradiated hepatocytes and downregulation of apoptosis by I B antisense oligonucleotides was mediated by suppression of caspases-9 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 38 publications
(34 reference statements)
0
8
0
Order By: Relevance
“…In contrast, temporarily blocking apoptosis (e.g., via caspase-inhibitors), may eliminate straindependent differences without reducing the radiation effect. Caspases 8 and 9 appear to be particularly promising targets as they have already been implicated in radiation-induced apoptosis in rat hepatocytes (Gurleyen et al 2009). As the primary difference between these two strains in terms of their radiation response seems to involve susceptibility to apoptosis, normalisation of apoptosis should eliminate the straindependent dose responses.…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, temporarily blocking apoptosis (e.g., via caspase-inhibitors), may eliminate straindependent differences without reducing the radiation effect. Caspases 8 and 9 appear to be particularly promising targets as they have already been implicated in radiation-induced apoptosis in rat hepatocytes (Gurleyen et al 2009). As the primary difference between these two strains in terms of their radiation response seems to involve susceptibility to apoptosis, normalisation of apoptosis should eliminate the straindependent dose responses.…”
Section: Discussionmentioning
confidence: 98%
“…Cells were irradiated with 6 MV photons at a dose rate of 2.4 Gy/min using a Varian Clinac 600 C accelerator (Varian, Palo Alto, CA, USA) as described previously (26–28, 34, 35, 38). Radiation doses of 2, 4, 8 and 25 Gy were applied.…”
Section: Methodsmentioning
confidence: 99%
“…Our data revealed that the pro‐inflammatory cytokine TNF‐α is of particular interest in the processes taking place after liver irradiation as radiation causes hepatocytes to become susceptible to TNF‐α‐mediated apoptosis (35). Therefore, radiation‐induced apoptosis of liver macrophages, Kupffer cells, may lead to a release of TNF‐α in the microenvironment (35) followed by apoptosis of the irradiated hepatocytes by radiation‐induced upregulation of IκB expression (38).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, TGF-b was not upregulated to such an extent in our model within the first 48 hours after irradiation (maximum threefold). Radiation-induced cytokine expression, on the one hand, influences cell viability of hepatocytes because in vitro experiments have shown that irradiation leads to susceptibility of hepatocytes to TNF-alpha mediated apoptosis (5,6). On the other hand, radiation-induced cytokine expression also influences gene expression (4,7,8), and liver metabolism as has been shown exemplary for disturbed iron metabolism after liver irradiation (7).…”
mentioning
confidence: 95%